1996
DOI: 10.1073/pnas.93.19.10519
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate transporters from the higher plant Arabidopsis thaliana.

Abstract: Two cDNAs (AtPT1 and AtPT2) encoding plant phosphate transporters have been isolated from a library prepared with mRNA extracted from phosphatestarved Arabidopsis thaliana roots. The encoded polypeptides are 78% identical to each other and show high degree of amino acid sequence similarity with high-affinity phosphate transporters of Saccharomyces cerevisiae, Neurospora crassa, and the mycorrhizal fungus Glomus versiforme. The AtPT1 and AtPT2 polypeptides are integral membrane proteins predicted to contain 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
339
2
12

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(361 citation statements)
references
References 31 publications
8
339
2
12
Order By: Relevance
“…Published reports indicate that, in response to P deficiency, plants may increase synthesis of additional transporter molecules (Drew et al, 1984) or upregulate expression of genes encoding P transporters (Liu et al, 1998;Muchhal et al, 1996;Smith et al, 1997), leading to a subsequent increase in transporter proteins (Muchhal and Raghothama, 1999). The increase of As(V) uptake with P deficiency has been found by Wang et al (2002), which showed that 8 d of P starvation increases the maximal influx of As(V) by 2.5-fold, suggesting an increased density of P/As(V) transporters in the rhizoid cell plasma membranes.…”
Section: Scanning Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Published reports indicate that, in response to P deficiency, plants may increase synthesis of additional transporter molecules (Drew et al, 1984) or upregulate expression of genes encoding P transporters (Liu et al, 1998;Muchhal et al, 1996;Smith et al, 1997), leading to a subsequent increase in transporter proteins (Muchhal and Raghothama, 1999). The increase of As(V) uptake with P deficiency has been found by Wang et al (2002), which showed that 8 d of P starvation increases the maximal influx of As(V) by 2.5-fold, suggesting an increased density of P/As(V) transporters in the rhizoid cell plasma membranes.…”
Section: Scanning Sitementioning
confidence: 99%
“…P has been considered to be acquired by plants through an energy-mediated transport process (Muchhal et al, 1996). Until now, there has been no direct study of the pattern of As transport into P. vittata rhizoids.…”
Section: Introductionmentioning
confidence: 99%
“…To monitor Piregulated gene expression, we used gene probes coding for an acid phosphatase (AtACP5), a Pi transporter (AtPT2), and a protein of unknown function (At4). These genes are induced by Pi limitation but are repressed in high Pi (Muchhal et al, 1996;del Pozo et al, 1999;Burleigh and Harrison, 1999). Seeds were germinated for 3 d on ϩPi medium and then transferred to ϩPi, ϪPi, and ϪPi/ϩPhi medium.…”
Section: Phi Selectively Represses Phosphate Starvationinducible Genementioning
confidence: 99%
“…RNA hybridization analysis with various 32 Plabeled probes, AtACP5 (del Pozo et al, 1999), At4 (Burleigh and Harrison, 1999), AtPT2 (Muchhal et al, 1996), and IAA1 and IAA3 (Abel et al, 1995), was carried out as described by Abel et al (1995). Equal RNA loading was assessed by hybridization with a rice (Oryza sativa) 17S ribosomal DNA probe.…”
Section: Isolation Of Nucleic Acids and Rna Hybridization Analysismentioning
confidence: 99%
“…This includes transporters from potato (StPT1 and StPT2) (Leggewie et al, 1997), Arabidopsis thaliana (AtPT1 and AtPT2) (Muchhal et al, 1996;, Medicago truncatula (MtPT1 and MtPT2) (Liu et al, 1998b) and tomato (LePT1 and LePT2) (Daram et al, 1998;Liu et al, 1998a). The encoded proteins share between 75 and 85% identity at the amino acid level and are distinct from PHT2;1.…”
Section: Introductionmentioning
confidence: 99%